Correction for May, Memorial to Bill Hamilton - R. M. May (Philosophical Transactions of the Royal Society of London. Series B: Biological Sciences, 2001)
Abstract Correction for ‘Memorial to Bill Hamilton’ by R. M. May (Phil. Trans. R. Soc. Lond. B 356, 785–787. (doi: 10.1098/rstb.2001.0885)). On page 785, the digital object identifier should read 10.1098/rstb.2001.0885.